CYPERACEAE: FICINIA LUCIDA: AN INTERSPECIFIC HYBRID BETWEEN F. CEDARBERGENSIS AND F. IXIOIDES SUBSP. GLABRA - T. H. Arnold (Bothalia: African Biodiversity & Conservation, 1981)
FICINIA LUCIDA: AN INTERSPECIFIC HYBRID BETWEEN  F. CEDARBERGENSIS AND F. IXIOIDES SUBSP.  GLABRA